2021
DOI: 10.1039/d1ta02870g
|View full text |Cite
|
Sign up to set email alerts
|

Designing for conjugate addition: an amine functionalised quinone anolyte for redox flow batteries

Abstract: Redox flow batteries (RFBs) are promising grid-level electrical storage systems. The key to this emerging technology is the development of cheap, highly soluble, and high energy-density inorganic and organic electrolytes....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Ions matching the accurate mass of a phoenicin dimer, trimer (9), tetramers (11), and pentamer (12) were observed. Additionally, ions corresponding to the dimer, trimer, and tetramer with an additional hydroxyl group were observed (7,8,10). Thus, we observed masses corresponding to phoenicin with additional hydroxyl groups and different stages of polymerization.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Ions matching the accurate mass of a phoenicin dimer, trimer (9), tetramers (11), and pentamer (12) were observed. Additionally, ions corresponding to the dimer, trimer, and tetramer with an additional hydroxyl group were observed (7,8,10). Thus, we observed masses corresponding to phoenicin with additional hydroxyl groups and different stages of polymerization.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
“…10−12 Besides benzoquinones, the anthraquinones, which have a multicyclic aromatic structure, have attracted the most attention with one of the most investigated quinones as RFB negolyte being the 9,10anthraquinone-2,7-disulfonic acid (AQDS). 7,11,13,14 Even AQDS, which shows reasonable stability, possibly due to having two additional aromatic rings, 10 aggregates when dissolved by dimerization with its hydroquinone form producing a quinhydrone, or by dimerizing with another AQDS molecule. 8,15 It has been shown that the storage capacity of the self-dimerized AQDS is less than the two electrons per molecule of AQDS that is usually reported.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The target solubility for organic electrolytes in aqueous RFBs for a commercially viable system is 2 m , but the vast majority of currently explored organic electrolytes struggle to meet this [6] . This balance between solubility and stability is a difficult tightrope to traverse, especially since the mere introduction of a solubilising functionality onto the anolyte or catholyte framework can result in decreased cycling stability or complete loss of electrochemical activity [7–9] . Nonetheless, the overall advantages of safety (due to the aqueous electrolyte), cost, and fast kinetics make the development of aqueous organic RFBs (AORFBs) an important area of study.…”
Section: Introductionmentioning
confidence: 99%
“…[18] As opposed to vanadium-based RFB systems, AORFBs employ electrolytes based on organic redox-active species from earth-abundant elements. [19] Among the most well-investigated compounds for AORFBs are quinones, which includes systems using anthraquinones, [20][21][22][23][24] benzoquinones, [5,25,26] and naphtoquinones, [27,28] viologens, [29][30][31][32] TEMPO-based (2,2,6,6tetramethylpiperidine-1-oxyl) organic radicals, [33][34][35][36] and ferrocenes, [6,37] as well as others. [38][39][40][41] The high interest in quinones as active materials in RFB electrolytes is based on both their ability to feature reversible two-electron redox reactions [42] and their structural diversity.…”
Section: Introductionmentioning
confidence: 99%